Normalization of Adolescent Casual Sexual Behavior: A Peircean Semiotic Analysis of Bincang Ranjang YouTube Content - Julianto, Callista Patricia; Yudhi, Lim (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The increasing prevalence of casual sexual behavior among Indonesian adolescents has become a pressing concern, especially as social media platforms like YouTube present open narratives about sexuality. In the context of limited sex education and persistent cultural taboos, this study analyzes how the normalization of adolescent casual sexual behavior is represented in the YouTube channel Bincang Ranjang, focusing on the episode “Yang Penting Tiap Hari.” Using a qualitative interpretive approach and Charles Sanders Peirce’s semiotic theory, this research examines eleven selected scenes to identify the sign (representamen), object, and interpretant. The study also incorporates symbolic interactionism to explore how meaning is constructed through social interaction and media engagement. The findings reveal that verbal and non-verbal signs, such as facial expressions, gestures, and casual dialogue, represent casual sex as enjoyable, ordinary, and an acceptable part of adolescents’ identity exploration. The open and permissive interaction between the guest and host reinforces these representations without critical reflection or educational framing. Audience responses further demonstrate how meaning is negotiated and contested, highlighting generational and cultural tensions as well as peer validation. Through symbolic interactionism, this study illustrates how adolescents may internalize such narratives as part of social learning and identity formation. This study concludes that the episode contributes to the normalization of adolescent casual sexual behavior by framing it as personal freedom and emotional autonomy. Therefore, the findings emphasize the urgency of strengthening media literacy and critical sex education, enabling adolescents to interpret sexual content more reflectively, ethically, and responsibly.